The Effect of Neuroticism on Vigilance Performance: A Transcranial Doppler Investigation. (September 2014) - Mandell, Arielle; Becker, Alexandra; VanAndel, Aaron; Nelson, Andrew; Shaw, Tyler H.
Selecting for vigilance assignments remains an important factor in human performance research. Recent research using personality measures as selection criteria has revealed mixed results in the predictive utility of personality on vigilance performance. The current study revisits the potential relationship between vigilance performance and one personality facet, trait neuroticism, in light of two opposing theories. The first theory suggests that neuroticism reduces vigilance performance due to an increase in self-referential worry. The second posits that neurotics can compensate for increased worry and other distractions by allocating increased attentional effort to the task, resulting in similar or improved performance. Neuroticism was assessed using the neuroticism facet of the NEO-PI-R. Using Transcranial Doppler Sonography, cerebral blood flow velocity (CBFV) was measured during completion of a 12-minute abbreviated vigilance task. Performance and CBFV data indicate that 1) high and low neuroticism participants displayed similar performance, and 2) a higher neuroticism score is associated with higher CBFV levels in the first period and a greater CBFV decrement over time on task. The association between neuroticism and high CBFV levels indicates that these individuals were recruiting additional cognitive resources in order to achieve similar performance to participants who are lower in neuroticism. Results are discussed in terms of theories that suggest that high levels of neuroticism can result in similar performance by allowing for increased on-task effort allocation at the cost of increased resource expenditure.